Pakistani postgraduate students' orientations for learning English as a second language: A factor analytic study. (July 2015) - Ali, Mansoor; Wyatt, Mark; Van Laar, Darren
Abstract: Given that the higher-level goals or 'orientations' of second language learners impact their motivation to learn, they are of consequent interest to researchers. Once conceptualized simply as either 'integrative' or 'instrumental', these orientations are increasingly understood to be more complex, particularly since the L2 in question is often English; as a global lingua franca, English is extending its range of functions around the world, while also becoming 'deterritorialized'. In contexts such as Japan and Pakistan, the latter the setting for this study, new orientations have recently been identified. However, research methods employed have not always included factor analytic techniques, which are particularly valuable for finding underlying structures in complex data. 500 postgraduates in a public university in North-Western Pakistan were surveyed and their responses subjected to factor analysis. 11 factors were identified: 'Education-Prestige', 'Identification', 'Receptive L2 Use for Non-Professional Purposes', 'Further Study-Work Abroad', 'Media-Instrumental', 'Travel-Friendship', 'Extrinsic-Ideal L2 Self', 'Business', 'National Interest', 'Intrinsic', 'International Posture and Learning L2 for Local Purposes'. Findings confirm the newly-discovered 'National Interest' orientation in this context and point towards the emergence of an 'L2 Indigenous Integrative' orientation that relates to using L2 for local purposes. Theoretical, methodological and pedagogical implications are discussed.